From Corporate Board to Balance Sheet: Board Characteristics and Financial Performance of Commercial Banks in Nepal - Sharma, Resham Raj (Prithvi Journal of Research and Innovation, 2023)
This study aims to examine the impact of board characteristics on the financial performance of commercial banks in Nepal. The study utilized census sampling of all commercial banks having shares listed and actively traded in the secondary market, NEPSE. Descriptive and inferential tools were employed including multiple linear regression models to analyze the impact of board characteristics on financial performance based on the longitudinal data of 21 commercial banks collected from the secondary sources over the period of ten years from 2013 to 2022. The study shows that strictly followed mandatory requirements regarding board size, board independence, and board committees after the enforcement of BAFIA in 2017 along with a relatively small representation of women and independent directors in the boardroom during the study period. The findings show a statistically significant negative impact of board diversity and board committees along with an insignificant impact of board size and board independence on ROA and ROE. The findings of the study also indicate that a higher proportion of women directors and a large number of board committees in the board have contributed negatively to the financial performance of commercial banks in Nepal. However, the comprehensive outcome of this research challenges the agency theory and points towards the presence of tokenism in the inclusion of women and independent directors. The results of the descriptive analysis assimilate to the agency and stakeholder theory respectively by ROE and ROA. The findings of this study have practical implications for banking regulators, legislators, and banks in policy formulation relating to board characteristics.